Kompensacyjne wychowanie kulturalne jako nowa tendencja w procesie akulturacji wychowanków placówki opiekuńczo-wychowawczej = Compensatory cultural education as a new trend in the pupils' acculturation process of a care and educational institution - Wagner-Tomaszewska, Teresa (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article focuses on the psychological competences of teachers-artists working with children, youth, as well as students of music schools and universities. Psychological competences are presented in the context of a wide range of didactic and specialist competences. Their possession and development is a factor conditioning the capability, efficiency, and correctness in executing an optimal teacher-student relation, and in the case of artistic education the master-student relation.
Keywords: nauczyciele; kompetencje; psychologia; pomoc; uczeń; rozwój; teacher; competences; psychology; support; students; development